SOCIO-CULTURAL PERSPECTIVES FOR SUSTAINABLE DEVELOPMENT OF INFRASTRUCTURE IN RURAL AREAS OF INDIA - Dillip Kumar DAS (Journal of Construction Project Management and Innovation)
Infrastructure is the backbone of the society for socio-economic development in rural India. In the past two decades, a large-scale development of social and economic infrastructure, such as schools, roads, water harvesting structures, community centres, and houses have been undertaken, particularly in the Community Development Blocks (administrative units for rural development) of India. However, despite various measures, such as availability of finances, work forces and development guidelines, it is argued that the development of infrastructure does not occur at the desired level. Therefore, using the case study of the Community Development Blocks in Odisha State of India this investigation examined the impediments for development of infrastructure; and how sustainable development of infrastructure in rural areas of India can be attained by using a cultural theory inspired socio-cultural perspective. A survey research method and stakeholders’ discussion were followed to conduct the study. Findings suggest that provision of finance, materials, equipment, availability of human resources and administrative guidelines do not alone ensure sustainable development of infrastructure. Non-effective or marginal engagement of appropriate stakeholders, disagreement and wrangle among local political leaders, and bureaucratic bottlenecks are the major impediments in the development process. However, it is also revealed that a deliberative constructive engagement and trade-offs and decisions based on concessions than consensus among the various stakeholders will enable smooth development process and construction of infrastructure in rural India. Consequently, a cultural theory inspired active and constructive engagement among the various social solidarities is advocated that would essentially generate the dynamics and cohesion among the stakeholders for sustainable development of infrastructure in rural areas in India.